Reverse transcriptional profiling: non-correspondence of transcript level variation and proximal promoter polymorphism. - Brown, R.P.; Feder, M.E. (BMC Genomics, 2005)
Variation in gene expression between two Drosophila melanogaster strains, as revealed by transcriptional profiling, seldom corresponded to variation in proximal promoter sequence for 34 genes analyzed. Two sets of protein-coding genes were selected from pre-existing microarray data: (1) those whose expression varied significantly and reproducibly between strains, and (2) those whose transcript levels did not vary. Only genes whose regulation of expression was uncharacterized were chosen. At least one kB of the proximal promoters of 15-19 genes in each set was sequenced and compared between strains (Oregon R and Russian 2b).Of the many promoter polymorphisms, 89.6% were SNPs and 10.4% were indels, including homopolymer tracts, microsatellite repeats, and putative transposable element footprints. More than half of the SNPs were changes within a nucleotide class. Hypothetically, genes differing in expression between the two strains should have more proximal promoter polymorphisms than those whose expression is similar. The number, frequency, and type of polymorphism, however, were the same in both sets of genes. In fact, the promoters of six genes with significantly different mRNA expression were identical in sequence.For these genes, sequences external to the proximal promoter, such as enhancers or in trans, must play a greater role than the proximal promoter in transcriptomic variation between D. melanogaster strains.